Measurement of dielectric constant of paint coated aluminium panel through microwave non destructive testing at frequency 18 to 26GHz (K Band) / Bibi Nawsheen Ebrahim Saib - Ebrahim Saib, Bibi Nawsheen (2009)
Microwave non destructive testing of paint and primer in components used in moist environment are crucial in the investigation of corrosion. This thesis presents a method for measuring the dielectric properties of corrode and non-corrode paint coated aluminium panels using metal-back method. The complex reflection coefficient Sn (real and imaginary) is measured using the Vector Network Analyzer (VNA). The dielectric constant and loss factor were measured for both corrode and non-corrode paint coated aluminium panels in the range of frequency from 18 to 26 GHz (K-Band) and the loss tangent was calculated. The thru, reflect and line (TRL) calibration technique were used to eliminate the effect of undesirable multiple reflection. The measurement system consists of Vector Network Analyzer (VNA), a pair of spot focusing horn lens antenna, mode transitions, coaxial cable and computer. A computer program was developed for calculating the complex reflection coefficient. The data obtained from the VNA measurement is sent to the program, which calculates the dielectric constant and loss tangent. The results show a significant difference in the dielectric properties of corrode and non-corrode paint coated aluminium panels.